Environmental regulation, green credit, and farmers’ adoption of agricultural green production technology based on the perspective of tripartite evolutionary game - Zuo, Zhi Ping (Frontiers in Environmental Science, 2023)
The adoption of agricultural green production technologies (AGPT) is crucial for achieving agricultural green development in developing countries. This paper establishes a tripartite game model to explore the evolutionary influence mechanism of government environmental regulation policies and bank green credit policies on farmers' adoption of AGPT under different initial conditions and strategy choices. Through theoretical analysis and numerical simulation, systematically deduce the evolutionary path and equilibrium conditions, as well as examine the synergistic evolutionary effect of these policies. The results demonstrate that government environmental regulation and bank implement the green credit policies effectively encourage farmers to adopt AGPT. However, conflicts may arise during the dynamic evolution process when banks choose to implement the green credit strategy. These conflicts can be mitigated by utilizing market-oriented mechanisms such as loan interest rates, improving bank supervision efficiency, and enhancing farmers' expected income. The findings of this research provide valuable insights into the development of external incentive mechanisms to promote the adoption of AGPT among farmers and foster green agricultural development.